2013
DOI: 10.1186/1757-7241-21-47
|View full text |Cite
|
Sign up to set email alerts
|

New pre-arrival instructions can avoid abdominal hand placement for chest compressions

Abstract: ObjectiveTo investigate if modified pre-arrival instructions using patient’s arm and nipple line as landmarks could avoid abdominal hand placements for chest compressions.MethodVolunteers were randomized to one of two telephone instructions: “Kneel down beside the chest. Place one hand in the centre of the victim’s chest and the other on top” (control) or “Lay the patient’s arm which is closest to you, straight out from the body. Kneel down by the patient and place one knee on each side of the arm. Find the mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 29 publications
1
13
0
2
Order By: Relevance
“…The different study designs, interventions and types of data presentations in included articles precluded further meta-analysis. For example, the authors tried to evaluate whether changing some instructional content of telephone dispatcher-assisted CPR would improve bystander CPR quality in some included studies, but those changes were different among studies [22,26,27,3335,37,40,41,52]. In other studies, the authors tried to compare the effect of compression-only CPR with that of conventional CPR on bystander CPR quality, but they presented different types of outcome data [18,25,32].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The different study designs, interventions and types of data presentations in included articles precluded further meta-analysis. For example, the authors tried to evaluate whether changing some instructional content of telephone dispatcher-assisted CPR would improve bystander CPR quality in some included studies, but those changes were different among studies [22,26,27,3335,37,40,41,52]. In other studies, the authors tried to compare the effect of compression-only CPR with that of conventional CPR on bystander CPR quality, but they presented different types of outcome data [18,25,32].…”
Section: Resultsmentioning
confidence: 99%
“…Among 42 studies included, 32 were RCTs, 6 studies [18,36,45,54,55,57] were randomized crossover controlled trials and 4 studies [24,48,49,53] were non-randomized studies. There were 13 studies conducted in North America [18,2224,34,35,37,40,44,49,52,53,58], 19 in Europe [17,2527,2931,33,38,39,4143,45,46,48,51,55,57], and 10 in the Asia-Pacific region [1921,28,32,36,47,50,54,56]. The years of publication ranged from 1989 to 2018.…”
Section: Resultsmentioning
confidence: 99%
“…In this study, eight lay rescuers performed CPR with abdominal hand placement. Instructions for hand placement have been changed throughout the guidelines updates20 and have resulted in a significant rate of incorrect hand placement 21, 22. Birkenes et al .…”
Section: Discussionmentioning
confidence: 99%
“…Birkenes et al . observed that lay people understood the center of the chest to be the same as the center of the torso20 and nearly half of their study participants who learned CPR even 6–9 months ago placed their hands too low 21. Guidelines claim that CPR by lay rescuers is quite safe even for victims who are not in CA 23, 24.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation